MEMBANGUN KNOWLEDGE MANAGEMENT SYSTEM UNTUK MEMBENTUK KNOWLEDGE SHARING MENGGUNAKAN METODE KM-ROADMAP - Nainggolan, Esron Rikardo (LPPM Universitas Nusa Mandiri, 2015)
The purpose of this research is to build the knowledge management system on supporting the sharing culture of theology between teachers and students in STTLB so that it can improve the quality of education at STTLB. Application of current knowledge management system is needed in every aspect in education. The ability of each institution in managing knowledge becomes its own power for the institution to be able to compete in improving education in Indonesia. In High School Cross-Cultural Theology, it is also very necessary to be applied due to the time and place for the sharing of limited knowledge about theology. The application of knowledge management system that is intended is to support the sharing of culture on the theology faculty and students in order to create new innovations that can support and improve the quality of the knowledge. The application is by using the Learning Management System (LMS) Moodle. The method used to determine the needs and describe conditions of STTLB through observation. Designing knowledge management systems is by using KM- Roadmap method